Various Aspects of Silicon Polymer Chemistry A Themed Issue in Honor of Professor Julian Chojnowski on the Occasion of His 85th Birthday - Rubinsztajn, Sławomir; Cypryk, Marek; Stanczyk, Wlodzimierz (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
This special issue of Molecules is dedicated to Professor Julian Chojnowski on the occasion of his 85th birthday for his outstanding achievements in the field of organosilicon chemistry. This issue contains one review and eleven original articles written by eminent experts on various aspects of silicon polymer chemistry, which reflect the tireless passion of Professor Chojnowski to the development of organosilicon chemistry.